Fitoplazma fertőzöttség vizsgálata kajszi ültetvényekben - Czotter, Nikoletta; OLáh, Beatrix; Petres, Martin; Baráth, Dániel; Szabó, Luca; Kirilla, Zoltán; Kocsisné Molnár, Gitta; Kocsis, László; Preininger, Éva; Lakatos, Tamás; Szabó, Zoltán; Várallyay, Éva (GEORGIKON FOR AGRICULTURE, 2017)
Plant diseases caused by phytoplasmas are serious problems for fruit growers all over the world, their role have been growing significantly in recent years. European stone fruit yellows caused by these type of plant pathogens endangers stone fruit species, especially apricot in our country. During our work we examined phytoplasma infection at the most important apricot growing regions in Hungary. Leaf samples were collected and DNA was extracted for PCR based detection. We used different sets of primers to detect and distinguish their presence in our samples. During our survey we have found widespread distribution of European stone fruit yellows phytoplasma in our apricot orchards. Beside of highly conservative genes our analysis was broaden to other more variable ones which made it possible to investigate relationships between strains.
Keywords: phytoplasma; Can. Phytoplasma prunorum; ESFY; apricot; stone fruits